2012
DOI: 10.1021/jm201217q
|View full text |Cite
|
Sign up to set email alerts
|

Binding Affinity Prediction for Ligands and Receptors Forming Tautomers and Ionization Species: Inhibition of Mitogen-Activated Protein Kinase-Activated Protein Kinase 2 (MK2)

Abstract: Treatment of ionization and tautomerism of ligands and receptors is one of the unresolved issues in structure-based prediction of binding affinities. Our solution utilizes the thermodynamic master equation, expressing the experimentally observed association constant as the sum of products, each valid for a specific ligand–receptor species pair, consisting of the association microconstant and the fractions of the involved ligand and receptor species. The microconstants are characterized by structure-based simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Autodock was used for this work, after we compared several different docking programs for how well they were able to reproduce the position within the active site of analogues of ATP compared to that of the crystal structure. This work revealed that that the protonation state of inhibitors had a pronounced effect on docking, consistent with work by others [25]. From about 5000 compounds chosen in our initial screening of the NCI and ZINC libraries, about 20 purchasable compounds were assayed as described below.…”
Section: Pathway To Discovering a Family Of Inhibitors Of Efsupporting
confidence: 83%
“…Autodock was used for this work, after we compared several different docking programs for how well they were able to reproduce the position within the active site of analogues of ATP compared to that of the crystal structure. This work revealed that that the protonation state of inhibitors had a pronounced effect on docking, consistent with work by others [25]. From about 5000 compounds chosen in our initial screening of the NCI and ZINC libraries, about 20 purchasable compounds were assayed as described below.…”
Section: Pathway To Discovering a Family Of Inhibitors Of Efsupporting
confidence: 83%
“…Natesan et al developed the QM/MM-Linear Interaction Energy approach to account for multiple ligand tautomers and protomers. [44] They applied single-point B3LYP/6-31G*/AMBER level of theory to 66 inhibitors of MAPK-activated protein kinase. This protocol resulted in improving the correlation between calculated and experimental binding affinities (R 2 ) from 0.66 to 0.91.…”
Section: Combination Of Scoring With Quantum Mechanics Calculationsmentioning
confidence: 99%
“…While QM methods currently provide mostly auxiliary tools, mainly for rescoring of docked or MD-derived binding modes, their great potential of improving binding affinity prediction is exemplified in the studies discussed earlier. [44,59,60,96,97] The first first-principles-based function, [59] the derivation of which required no fitting to experimental data, may well be manifesting the beginning of a new era in docking research, where hardware and algorithm developments make it possible to apply first-principles theoretical treatment to affinity predictions. Free from approximations and simplifications associated with force-field, empirical, and knowledge-based scoring functions and implicit solvent rescoring methods, QM calculations offer opportunities for target-independent treatment of protein-ligand systems, including incorporation of polarizability and binding-associated ligand strain.…”
Section: Concluding Remarks On Trends and New Ideasmentioning
confidence: 99%
“…We prefer to use the Linear Response (LR) method in our quantum mechanics/molecular mechanics (QM/MM) modification [81-85] because of a favorable cost/performance ratio and the ability to cope with polarized H-bonds and electrostatic interactions, coordination bonds, and other interactions that cause problems when classical force fields are deployed. The procedure starts with best docked poses, which have the geometry and charges optimized by a QM/MM approach, and performs the conformational space mapping by a force-field based molecular dynamics (MD) of the hydrated complex.…”
Section: Introductionmentioning
confidence: 99%
“…The multispecies QM/MM-LR approach was applied to 66 benzothiophene and pyrrolopyridine inhibitors of mitogen-activated protein kinase (MAPK)-activated protein kinase 2 (MK2) [85]. The compounds form a complex network of up to five tautomers and seven ionization species (233 species altogether), and the binding site is available in one ionization/tautomer species only.…”
Section: Introductionmentioning
confidence: 99%